iSupport for rare dementias: a mixed-methods non-randomised feasibility study of an online self-help programme for carers - Bethan Naunton Morgan; Gill Windle; Carolien Lamers; in collaboration with the Rare Dementia Support (RDS) Impact project research team (Pilot and Feasibility Studies)
Abstract Background iSupport for dementia carers is an online education and self-care programme developed by the World Health Organisation for carers of people with the most common forms of dementia (Alzheimer’s disease and vascular dementia). iSupport for rare dementias (RDC) is the first adaptation designed specifically to address the challenges faced by carers of individuals with rare dementias (frontotemporal dementia, posterior cortical atrophy, primary progressive aphasia or Lewy body dementia). Methods A 12-week mixed-methods non-randomised feasibility study assessed the feasibility of recruitment and participant retention, the feasibility of outcome measures and the acceptability of iSupport RDC. Participants were recruited through the Rare Dementia Support Network (target N = 30). Data were collected through online interviews and self-report, including pre and post-intervention measures of depression, anxiety, burden and resilience. A modified version of the NoMAD questionnaire evaluated acceptability of implementation. Scores range from 0 to 4 with > / = 2.5 indicating acceptability. Usability was assessed through self-report and data from Blackboard. Results Thirty-four (13 males and 21 females) carers of people with frontotemporal dementia, posterior cortical atrophy, primary progressive aphasia or Lewy body dementia consented to the study and given access to iSupport RDC, hosted online by Blackboard Learn. Their ethnicity was reported as white and their mean age was 64.2 (range 35–86). N = 24 completed pre and post outcome measures, N = 10 completed pre-intervention and then withdrew, n = 4 reporting technical difficulties (70.6% completion rate). There were no missing responses. N = 20 completed 3 of the 5 iSupport RDC modules; n = 13 completed five. N = 4 could not access due to technical difficulties. Technical difficulties meant the data from Blackboard Learn were not obtained. The NoMAD total score (3.5) indicated iSupport RDC was acceptable. Qualitative analysis from n = 19 participants revealed themes of ‘technical difficulties’ (n = 10), ‘useful and informative’ (n = 7), and ‘provide at point of diagnosis’ (n = 5). Conclusions Recruitment targets were met but there were limitations in sample diversity. The extent of attrition warrants strategies to ensure retention to future studies, including testing online interventions on different internet browsers and operating systems. The favourable response to iSupport RDC from the participants indicates its potential as a valuable resource for supporting carers dealing with rare dementias.